Is a cancer diagnosis associated with subsequent risk of transient global amnesia? - Jianwei Zhu; Donghao Lu; Olafur Sveinsson; Karin Wirdefeldt; Katja Fall; Fredrik Piehl; Unnur Valdimarsdóttir; Fang Fang (PLoS ONE, 2015)
Psychological stress has been associated with transient global amnesia (TGA). Whether a cancer diagnosis, a severely stressful life event, is associated with subsequent risk of TGA has not been studied.Based on the Swedish Cancer Register and Patient Register, we conducted a prospective cohort study including 5,365,608 Swedes at age 30 and above during 2001-2009 to examine the relative risk of TGA among cancer patients, as compared to cancer-free individuals. Incidence rate ratios (IRRs) and their 95% confidence intervals (CIs) derived from Poisson regression were used as estimates of the association between cancer diagnosis and the risk of TGA.During the study 322,558 individuals (6.01%) received a first diagnosis of cancer. We identified 210 cases of TGA among the cancer patients (incidence rate, 0.22 per 1000 person-years) and 4,887 TGA cases among the cancer-free individuals (incidence rate, 0.12 per 1000 person-years). Overall, after adjustment for age, sex, calendar year, socioeconomic status, education and civil status, cancer patients had no increased risk of TGA than the cancer-free individuals (IRR, 0.99; 95% CI, 0.86-1.13). The IRRs did not differ over time since cancer diagnosis or across individual cancer types. The null association was neither modified by sex, calendar period or age.Our study did not provide support for the hypothesis that patients with a new diagnosis of cancer display a higher risk of TGA than cancer-free individuals.